Mediatisasi Agama Dalam Dakwah Halimah Alaydrus di Media Sosial Instagram - Cholillah, Cholillah; Arju, Asa Nabila (Al-Qudwah, 2024)
The increasingly massive development of technology provides a gap in creating social discrepancies in society because it departs from the impact of understanding online media da'wah so that consumption is received personally without any prior review process. The process of finding this kind of understanding needs religious mediatization to avoid one-sided consumption in understanding da'wah content on social media. This research focuses on the object of study Halimah Alaydrus via her Instagram to be examined comprehensively with a qualitative approach and using the critical-analytical method. So that it departs from the Koran that it becomes a text that is always relevant from time to time both in terms of place and time, that the content that becomes the subjectivity of a Halimah Alaydrus gives a distinctive da'wah color and is easily understood by various groups. As for the results of this study, researchers found several verses that were used as da'wah content by Halimah Alaydrus which were persuasive in nature. In this case, the verse construction used provides orientation to the community to remain calm in living life, despite loneliness, focus on yourself, always feel that Allah is in control of His servants. It is at this point that Halimah Alaydrus inserts several strands of redaction that are in accordance with the current context in her caption. the space to simplify or simplify the interpretation of a verse ultimately becomes the impetus and needs of the community in understanding the content of the message of the Quranic verse. Of course, at the same time, the understanding of a verse will continue to move dynamically.Abstrak: Perkembangan teknologi yang kian masif memberikan celah dalam menciptakan diskrepansi sosial masyarakat karena berangkat dari dampak pemahaman dakwah media online sehingga konsumsi yang diterima secara personal tanpa adanya proses penelaahan terlebih dahulu. Proses untuk menemukan pemahaman semacam ini perlu adanya mediatisasi agama untuk menghindari konsumsi secara sepihak dalam memahami konten-konten dakwah di media sosial. Adapun penelitian ini momfokuskan kepada objek kajian Halimah Alaydrus via instagramnya untuk ditelaah secara komprehensif dengan pendekatan kualitatif dan menggunakan metode analisis-kritis. Sehingga berangkat dari Al-Qur’an bahwa menjadi teks yang selalu relevan dari masa ke masa baik dari sisi tempat ataupun waktu, bahwa kadungan yang menjadi subjektivitas seorang Halimah Alaydrus memberikan warna dakwah yang khas dan mudah dipahami oleh berbagai kalangan. Adapun hasil dari penelitian ini, peneliti menemukan beberapa ayat yang dijadikan konten dakwah oleh Halimah Alaydrus yang bersifat persuasif. Dalam hal ini kontruksi ayat yang digunakan memberikan orientasi kepada masyarakat untuk tetap tenang dalam menjalani kehidupan, meskipun rasa kesepian, fokus dengan diri sendiri, selalu merasa bahwa Allah dalam pengawan hamba-Nya. Pada titik inilah Halimah Alaydrus menyisipkan beberapa untaian redaksi yang sesuai dengan konteks kekinian dalam caption¬-nya. ruang untuk menyederhanakan atau simplikasi penafsiran pada sebuah ayat pada akhirnya menjadi dorongan dan kebutuhan masyarakat dalam memahami isi pesan ayat Al-Qur’an. Tentu pada saat yang sama, pemahaman atas suatu ayat akan terus bergerak secara dinamis.